1987
DOI: 10.1111/j.2044-835x.1987.tb01061.x
|View full text |Cite
|
Sign up to set email alerts
|

Infants' understanding of numerical transformations

Abstract: This research explored infants' understanding of transformations that change the numerosity of a set. Do infants know how the insertion or deletion of a single object affects the relative numerosity of two sets? Four age groups (14‐, 18‐, 24‐ and 28‐month‐olds) were tested on problems involving sets whose numerosities were never greater than 2. The children were encouraged to find the set with more objects, after watching the experimenter cover up two sets and then transform one of them by performing either an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Furthermore, a number of studies have investigated the development of addition and subtraction in toddlers and young preschoolers using dependent measures such as reaching, object manipulation, and verbal response (e.g., Houdé, 1997;Huttenlocher et al, 1994;Sophian & Adams, 1987;Starkey, 1992;Vilette, 1996;Vilette & Mazouz, 1998). Young children's performance on simple addition and subtraction tasks with very small sets of concrete objects indicate that by their second year children know the ordinal effect of these operations, that addition yields more and subtraction yields less (e.g., Sophian & Adams, 1987;Starkey, 1992). The ability to calculate the exact results of simple addition and subtraction problems, however, develops gradually during early childhood (e.g., Huttenlocher et al, 1994;Starkey, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a number of studies have investigated the development of addition and subtraction in toddlers and young preschoolers using dependent measures such as reaching, object manipulation, and verbal response (e.g., Houdé, 1997;Huttenlocher et al, 1994;Sophian & Adams, 1987;Starkey, 1992;Vilette, 1996;Vilette & Mazouz, 1998). Young children's performance on simple addition and subtraction tasks with very small sets of concrete objects indicate that by their second year children know the ordinal effect of these operations, that addition yields more and subtraction yields less (e.g., Sophian & Adams, 1987;Starkey, 1992). The ability to calculate the exact results of simple addition and subtraction problems, however, develops gradually during early childhood (e.g., Huttenlocher et al, 1994;Starkey, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…However, even though considerable interest in research on counting and addition principles emerged already in the 1980s and still continues (e.g., Baroody, 1984;Baroody & Gannon, 1984;Baroody et al, 1983;Briars & Siegler, 1984;Canobi, Reeve & Pattison, 1998, 2002, 2003Fuson, 1988;Gelman & Gallistel, 1978;Gelman & Meck, 1983;Resnick, 1992;Sophian & Adams, 1987;Starkey & Gelman, 1982), the central question has not been solved yet: How and when do children acquire integrated knowledge representations, in the sense of true formal arithmetic principles? For instance, Geary (2006) stated that it is not clear when children "explicitly understand commutativity as a formal arithmetical principle" (p. 791).…”
Section: 1mentioning
confidence: 99%
“…Cooper reported that 14-to 16-month-olds successfully discriminated both same/different and more/less relationships, but did not present data on performance with particular numerosities. Finally, Sophian and Adams (1987) gave children of 14, 18, 24, and 28 months choices between arrays of varying numerosity. With 1-versus-2 comparisons, the oldest and the youngest age groups chose the array with the greater numerosity.…”
mentioning
confidence: 99%